Measuring the impact of ACI Motors’ digital marketing strategies on brand perception in the generator industry - Bhuiyan, A.K.M. Akibuzzaman (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.